Efektifitas Anti Inflamasi Formulasi Kunyit (Curcuma Longa), Daun Binahong (Anredera Cordifolia) Dan Daun Sambiloto (Andrographis Paniculata) Terhadap Luka Sayat Pada Kelinci - Kh Endah Widhi Astuti; Sih Rini Handajani (Interest : Jurnal Ilmu Kesehatan, 2019)
Background: Perineal lacerations are tears that occur in the perineum because of the second stage of labor. The Javanese people do the purpose of this study is the effectiveness of the anti-inflammatory formulation of turmeric (Curcuma longa), leaves of Binahong (Anredera cordifolia) and leaves of Sambiloto (Andrographis paniculata) against incisions in rabbits. Method: The method used in this study is the method in this study. This research uses a quantitative method with a type of pure treatment research in the form of a pre-post test design. The sample in this study was 10 rabbits per group in 5 groups. Results: There was an anti-inflammatory effect of the turmeric formulation, binahong leaves of bitter leaf (F1, F2, and F3) in the incision wound in rabbits (ρ <0.001). There is an anti-inflammatory effect of turmeric formulation, binahong leaves of a bitter leaf on leukocyte levels in rabbit incisions in F1, F2, and F3 compared to the control group (ρ <0.001). Conclusion: Turmeric formula, binahong leaf, bitter leaf (F1, F2, and F3) in the incision in rabbits can improve the wound healing process.